2014
DOI: 10.1007/s10964-014-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of the Bidirectional Association Between Sleep Problems and Social Ties at University: The Mediating Role of Emotion Regulation

Abstract: Despite the growing body of research linking sleep problems and social ties, research investigating the direction of effects between these two constructs is lacking. Furthermore, there remains a dearth of research examining the mechanisms that may explain the association between sleep problems and social ties within a longitudinal design. The present 3-year longitudinal study addressed two research questions: (1) Is there a bidirectional association between sleep problems and social ties at university? and (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 69 publications
5
52
1
Order By: Relevance
“…Face-to-face interactions with friends may provide opportunities to experience positive affect (39), which subsequently promote good sleep. Time spent in-person with friends also had positive associations with sleep efficiency – particularly for younger adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Face-to-face interactions with friends may provide opportunities to experience positive affect (39), which subsequently promote good sleep. Time spent in-person with friends also had positive associations with sleep efficiency – particularly for younger adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although not focused on physical and physiological characteristics, the Tavernier and Willoughby (2015) study in this issue complements the Sladek and Doane (2015) study by examining the bidirectional associations between sleep problems and social connectedness. In a 3-year longitudinal study of 942 university students Tavernier and Willoughby (2015) found that sleep quality was prospectively associated with more positive social ties and that this association was mediated by emotion regulation. In addition, cascading processes emerged, as positive social ties contributed to more effective emotion regulation which in turn contributed to fewer sleep problems.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 99%
“…artificially shortened night sleep) on subsequent emotional functioning (Pilcher & Huffcut, 1996). For instance, a shortened night sleep among young adolescents has been associated with worse ER; this has been found when sleep loss is measured by actigraphy, (objective measurements of sleep-related somatic activity; Vriend et al, 2013), experimental deprivation (Baum et al, 2014), or self-reports (Tavernier & Willoughby, 2014). People who report poor sleep for the past week exhibit worse emotion-regulation ability in the laboratory (Mauss et al, 2013).…”
Section: Disordered Sleep and Emotion Regulation Abilitymentioning
confidence: 99%
“…Maladaptive ER has been shown to mediate processes related to individual adjustment, such as the relationship between sleep problems and detrimental social ties in university students (Tavernier & Willloughby, 2014) or between insomnia and negative mood (Xia & Zhou, 2010). Maladaptive ER has specifically predicted increased depressive symptoms at a five-year follow-up (Berking et al, 2014), and, conversely, endorsement of successful ER strategies predicts recovery from depression (Arditte & Joormann, 2011).…”
Section: Emotion Regulation and Depressionmentioning
confidence: 99%